Identification of Potential Landslides Area of Sukabumi, West Java Using Gravity Anomalies and Classification of Support Vector Machine - Abdurrohman Jauhari; Iskandarsyah (Jurnal Geosains Terapan, 2021)
Landslides are one of the natural disasters that have claimed many victims ranging from property to lives. In an effort to reduce losses caused by landslides, it is important to carry out disaster mitigation processes. Mitigation that will be discussed is in the form of identifying potential disaster zones using gravity geophysical methods and remote sensing. The research was conducted in the Sukabumi area, West Java, which is a densely populated area and part of the Bandung Zone and the Southern Mountain Zone according to Van Bemmelen (1949). The method used is the gravitational anomaly method with Second Vertical Derivative (SVD) analysis and optical image analysis with the Support Vector Machine (SVM) classification to produce a map of the distribution of landslide potential in the Sukabumi Regency.